Ludwig Wittgenstein : a memoir - Malcolm, Norman (Oxford University Press, 1984)
This moving and authoritative portrait of Ludwig Wittgenstein--one of the most powerful influences on contemporary philosophy--treats Wittgenstein the man, his unusual teaching methods, and his modes of thought and expression as seen through the eyes of Norman Malcolm, first as a student and later as a close personal friend. This new edition contains the complete text of fifty-seven letters written by Wittgenstein to Malcolm over a period of eleven years. Appearing in print for the first time in their entirety, these letters serve to illuminate Wittgenstein as a warm and concerned friend as he gives advice, teases, and offers sympathy.